Distributing Images and Information over the Web - a Case Study of the Pont Manuscript Maps - Fleet, Christopher (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
Technological changes in recent years have encouraged many libraries to deliver digital images of their materials over the Internet. For larger items, including maps, high resolution images of research quality can now be obtained from steadily cheaper equipment, computers can process larger images more comfortably, and newer compression formats have allowed these images to be viewed interactively online. The exponential growth of the Internet has also created a large body of users who wish to access these images from their homes or desktops. Within this context, this paper describes the scanning of the Pont manuscript maps of Scotland, the technology used to make these maps available over the Internet, and the initial stages of the construction of a website of associated information. This case study is not presented as a prescriptive example of best practice, but rather as an illustration of some of the main practical issues involved, using these to present arguments for and against current map digitisation and Web delivery work.